A review and meta-analysis of the survival rate of adult with osteonecrosis of the femoral head treated with transtrochanteric rotational osteotomy. Issue 47 (25th November 2022) - Xu, Yong; Zeng, Ping
Abstract : Background: Osteonecrosis of the femoral head (ONFH) is a progressive disease, and transtrochanteric rotational osteotomy (TRO) is a promising option to treat hip preservation. Compared with outcomes of non-Asian patients, those of Asian patients are different. Once ONFH has progressed to the stage of collapse, total hip arthroplasty (THA) is an unavoidable surgical procedure. However, patients treated with TRO still have a certain rate of femoral head collapse. A meta-analysis was done to comprehensively understand the outcome of TRO surgery for ONFH, in which conversion to THA was used as an endpoint event or the survival rate of patients with ONFH after TRO surgery as an indicator. Methods: We retrieved electronic databases from the inception of the study until June 2022, using the survival rate after TRO surgery or that after conversion to the endpoint event of THA as the effect indicator. The Risk Difference Independent unmatched samples of counting information with 95% confidence intervals (CI) were used to calculate the outcome. Also, subgroup analysis was carried out for Asian and non-Asian patients. Heterogeneity and publication bias analyses were also done for the included studies Results: We pooled 19 studies, all of which were about applying TRO procedure for ONFH. There were 15 cohort studies, 4 case-control studies, and no randomized controlled studies. Based on the information extracted from the reported above (we extracted the relevant independent effect values separately for the case-control studies), this meta-analysis was performed based on a fixed-effect model, and META analysis was performed for an independent unpaired group of the samples. The total hip survival rate after TRO in ONFH was 0.58(95% CI = 0.45–0.72), The survival rate for Asians was: 0.68 (95% CI = 0.51–0.85) and for non-Asians was: 0.41 (95% CI = 0.17–0.64), respectively. Conclusions: The application of TRO surgery in ONFH can effectively relieve patients' symptoms and they enjoy n a high survival rate, especially for Asian patients. This makes it a promising surgical technique.